2020
DOI: 10.1111/aos.14586
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of ocular abnormalities in a Chinese multicentre neonatal eye screening programme—1‐year result

Abstract: Purpose: Early detection of ocular abnormalities in newborns is essential for timely diagnosis and treatment. This study aimed to assess the 1-year result of a multicentre prospective neonatal eye examination programme with wide-field digital imaging system in China. Methods: A multicentre collaborative prospective study group for neonatal eye screening was established in nine hospitals, including eight Maternal and Children's Hospitals, and one general hospital across China from July 2016 to June 2017. Ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Among them the highest rate was retinal hemorrhage (RH) which accounted for 95.08% of all abnormalities. The results are basically consistent with those of Zhao Peiquan [1] . We found that the main reason why the overall ocular abnormality rate was lower in the NICU group (11.37%) than in the Control Group (18.24%) was that the positive rate of retinal bleeding (9.38%) was lower in NICU group than in the Control Group (17.80%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among them the highest rate was retinal hemorrhage (RH) which accounted for 95.08% of all abnormalities. The results are basically consistent with those of Zhao Peiquan [1] . We found that the main reason why the overall ocular abnormality rate was lower in the NICU group (11.37%) than in the Control Group (18.24%) was that the positive rate of retinal bleeding (9.38%) was lower in NICU group than in the Control Group (17.80%).…”
Section: Discussionsupporting
confidence: 90%
“…Early, accurate and comprehensive eye examination of newborns is a crucial step in prevention and treatment of blindness in children's vision care and in the society as a whole. Facilitating timely and effective intervention in all types of eye diseases in newborns within the optimal time window plays a key role in the physical and mental health of newborns [1] . Digital Wide Area Fundus Imaging System (RetCam 3 ) is well imaged, easy to operate and can record the eye situation objectively and accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Familial exudative vitreoretinopathy (FEVR) is a severe genetic disorder in which incomplete peripheral retina vascularization causes secondary complications, including neovascularization, vitreous hemorrhage, retinal folds, and retinal detachments (5). A survey of early ocular examinations conducted in 64,632 Chinese newborns within 9 hospitals unraveled an incidence rate of FEVR of approximately 4.4‰ (6). Among the known genes involved in FEVR, components of the Wnt signaling pathway are highly prevalent, including FZD4 (frizzled 4) (7), LRP5 (low-density lipoprotein receptor-related protein 5) (8,9), TSPAN12 (tetraspanin 12) (10)(11)(12), NDP (norrin, previously known as Norrie disease pseudoglioma) (13), LRP6 (low-density lipoprotein receptor-related protein 6) (14), and CTNNB1 (catenin beta 1) (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Several large studies have demonstrated the results of universal neonatal eye screening. Although the majority of findings were retinal haemorrhages, some babies who would not be screened routinely required further referral and treatment 19–22. Wide-field neonatal anterior and posterior eye imaging performed by a non-ophthalmologist and immediate image referral and analysis by an ophthalmologist in a tertiary centre might contribute to early diagnosis and increase coverage 23…”
Section: Introductionmentioning
confidence: 99%